Questões discursivas e sociais na alfabetização científica : um estudo crítico das erratas na revista Superinteressante - Santos, Paulo Sérgio da Silva (2012)
The critical study of errata offers great social contribution to the practice of consuming texts of scientific dissemination. Clearly there are, nowadays, a growing demand for information of a scientific nature, since people are being asked to show their points of view about important issues all the time: nuclear power, genetically modified foods, hormone replacement etc.. The magazines of science communication are occupying the place of "scientific literacy", and reach millions of readers every month. However, not yet identified a reflective discussion about this practice when considered, specifically, the identification and analysis of social and discursive errors published in these journalistic texts. Thus this thesis aims to reflect on the responsibility of the media to transmute the scientific discourse to the discourse of scientific dissemination, discussing the consequences of 'ownership' discourse in the context of reporting on science. We are concerned mainly with the frequency and importance of the misunderstandings between scientists and journalists and the discursive forms of interaction between readers and editors and their materialization in the errata. In the methodology, we follow the qualitative-interpretative guidance. We collect the corpus from the errata issues aired in April and October between 1988 and 2011 from SUPERINTERESSANTE magazine. Critical reflection was based on theoretical Critical Discourse Analysis. We seek to establish a dialogue between a version of ACD developed by Fairclough (1999, 2001, 2003), dialecticalrelational approach, and other disciplines such as Science Communication, Media and Systemic Functional Grammar through Appraisal System developed by Martin & White (2004). The results show that the popular science magazine in question has a frequency of errors that are not consistent with the role of "scientific literacy" claimed for it. It was proven, through errors of all levels that the interests of the journal detours the interests of readers who, in turn, does not have the instruments necessary to prove what they consume. Thus, we believe that this research provides an important contribution to the debate about the disclosure and use of scientific information in Brazil.